Seismotectonic Deformation from Focal Mechanisms of Earthquakes in the Valle del Cauca, Southwestern Colombia - Salcedo, Elkin de J. (2017)
Using data of focal mechanisms, we analyzed the seismotectonic strain regime in the Valle del Cauca, of southwestern Colombia. Were selected 49 earthquakes with magnitude Mw≥4.8 within the period of 1976 to 2010. This data was taken from ISC (International Seismological Center) and GCMT (Global Centroid Moment Tensor) database. According with the spatial distribution of different types of focal mechanisms, we recognize four main seismotectonic deformation zones: the seaward side of the trench (Environment-I), the bending and interplate interaction zone (Environment-II), the shallow continental zone (Environment-III), and the intermediate Benioff zone (Environment-IV). Overall, the geodynamic features of these environments are controlled by the subduction zone. We obtained that the bending zone has an angle of inclination of 30°, which generates a tangential deformation stress (ts) with a magnitude of 7.67*1022 Pa; a tangential force (Fs) of 1.06*1027 N/m, and a normal force (Fn) equivalent to 1.47*1028 N/m with a slab pull force of 1.57*1028 N/m. Moreover, the interplate seismic coupling coefficient is 0.21, suggesting a subduction zone of intermediate activity. On the other hand, the dislocation velocity (vs) and subsidence velocity (vd) of the oceanic plate are 3.68 cm/year and 2.76 cm/year, respectively. These geodynamic and kinematic characteristics explain the frequent seismic events of small to moderate intensity (2≤M≤5), and the occurrence of a possible earthquake with Mw≥7 magnitude in the region.